Pelatihan Aspek Akutansi Badan Usaha Milik Desa (BUMDes) Karya Harapan Bersama (KHB) Kuala Secapah Kabupaten Mempawah Dalam Membuat Laporan Pertanggungjawaban - Murad Murad (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. Various regulations that have been issued emphasize the independence of the Village and the independence of the Village in managing Village resources and sources of funds. The village as an autonomous region has exclusivity, among others, in terms of the authority to manage village finances independently, the authority to make village regulations, and the authority to make BUMDes. The objectives of this activity are: (a) To complete the capacity of BUMDes officers in managing financial transactions as the initial basis for preparing financial reports. (b) Improving the ability of BUMDes officers in completing and producing financial reports through the application of the accounting cycle. (c) Completing the ability of BUMDes officers in making financial reports as part of the BUMDes financial accountability report. Solutions and Outcomes: (1) Training on how to manage financial transactions such as journaling, making ledgers, trial balances. (2) Training on making financial reports through worksheets. (3) Financial reporting and accountability training. The output of the activities carried out was a change in attitude in terms of participants' understanding of BUMDes management and financial reporting after the delivery of materials and discussions during the training.Keyword: Village, BUMDes, Journaling, Trial balance, Work sheet